Role of Fatty Acids in Milk Fat and the Influence of Selected Factors on Their Variability-A Review - Hanuš, Oto; Samková, Eva; Křížová, Ludmila; Hasoňová, Lucie; Kala, Robert (Molecules (Basel, Switzerland), 2018)
Fatty acids (FAs) of milk fat are considered to be important nutritional components of the diets of a significant portion of the human population and substantially affect human health. With regard to dairy farming, the FA profile is also seen as an important factor in the technological quality of raw milk. In this sense, making targeted modifications to the FA profile has the potential to significantly contribute to the production of dairy products with higher added value. Thus, FAs also have economic importance. Current developments in analytical methods and their increasing efficiency enable the study of FA profiles not only for scientific purposes but also in terms of practical technological applications. It is important to study the sources of variability of FAs in milk, which include population genetics, type of farming, and targeted animal nutrition. It is equally important to study the health and technological impacts of FAs. This review summarizes current knowledge in the field regarding sources of FA variability, including the impact of factors such as: animal nutrition, seasonal feed changes, type of animal farming (conventional and organic), genetic parameters (influence of breed), animal individuality, lactation, and milk yield. Potential practical applications (to improve food technology and consumer health) of FA profile information are also reviewed.
Keywords: Lactation; organic system; mléko; energy status; season; genetic polymorphism; Animal Nutritional Physiological Phenomena; krmivo pro zvířata; breed; Fatty Acids; dairy cow; lactation; fyziologie výživy zvířat; ženské pohlaví; zvířata; Humans; nutrition; laktace; Animal Feed; Milk; mastné kyseliny; feeding; milk fatty acid profile; Female; lidé; Animals